Produção audiovisual como recurso didático-pedagógico no ensino de história : "Como me veem?", "Como eu vejo?" estudo de caso de adolescentes de uma comunidade em situação de vulnerabilidade social - Dall' Agnol, Caroline (My University, 2016)
This work, carried out between 2013 and 2015, falls within the context of an audiovisual production process that works with the concept of identity and belonging among adolescents in a socially vulnerable community in Caxias do Sul, RS. The Audiovisual Production study as a didactic and pedagogical resource in History teaching: "How do they see me?", "How do I see myself?" case study of adolescents from a socially vulnerable community has the general objective of developing a methodology, with the use of audiovisual production in History teaching, working the concepts of identity and belonging of teenagers from communities in socially vulnerable situation, on the premise that the audiovisual production allows the teenager to lie as protagonist in their social-historical-cultural context. While the didactic-pedagogic resource enables the young to take the place of historical subject, it also functions as a double mirror, strengthening self-knowledge and self-esteem (sense of identity) and triggering a social visibility process (recognition and feeling of belonging to the community in which they live). The problem of academic study that guides the work is if audiovisual production, as didactic and pedagogical resource in History teaching, can develop a sense of identity and belonging in adolescents from communities in socially vulnerable situation. The conducting vein to this research is structured in the development of the audiovisual production that meets the proposed social pedagogical education (humanizing education), when worked in class room and focused in the adolescent's insertion as the subject of history. In this way, the teenager gains space for reflection on a fundamental question: "How do they see me?" (Social visibility) "How do I see myself?" (Self-recognition), an issue that buoyed the choice and definition of the subject. Who guides us to seek those answers are the theoretical Honneth (2003), Freire (1996, 2004), Martin-Barbero (2003), Pêcheux (1999), Bourdieu (2010; 1974; 1983; 1972), Canclini (1984; 1999), Hall (2005) and Goffman (1988).
A presente dissertação, realizada entre 2013 e 2015, insere-se no contexto de um processo de produção audiovisual que trabalha com o conceito de identidade e pertença de adolescentes de uma comunidade em situação de vulnerabilidade social em Caxias do Sul, RS. O estudo Produção Audiovisual como recurso didáticopedagógico no Ensino de História : “Como me veem?”, “Como eu me vejo?” estudo de caso de adolescentes de uma comunidade em situação de vulnerabilidade social tem como objetivo geral desenvolver uma metodologia, com o uso da produção audiovisual no ensino de História, trabalhando os conceitos de identidade e pertença de adolescentes, partindo da premissa de que a produção audiovisual possibilita ao indivíduo situar-se como protagonista em seu contexto sócio-histórico-cultural. Ao mesmo tempo em que o recurso didático-pedagógico possibilita ao jovem ocupar o lugar de sujeito histórico, também funciona como um duplo espelho, fortalecendo o autoconhecimento e a autoestima (sentimento de identidade) e desencadeando um processo de visibilidade social (reconhecimento e sentimento de pertença à comunidade em que vive). O problema do estudo acadêmico que guia o trabalho é se a produção audiovisual, como recurso didático-pedagógico no Ensino de História, pode desenvolver o sentimento de identidade e pertença em adolescentes de comunidades em situação de vulnerabilidade social. A veia condutora dessa pesquisa está estruturada no desenvolvimento da produção audiovisual que, atende a proposta de educação pedagógica social (educação humanizadora), quando trabalhada dentro de sala de aula e focada na inserção do adolescente como sujeito da história. Desta forma, o adolescente ganha espaço para a reflexão sobre uma questão fundamental: “Como me veem?” (visibilidade social) “Como eu me vejo?” (autoreconhecimento), questão que balizou a escolha e definição do tema. Quem nos guia para buscar essas respostas são os teóricos Honneth (2003), Freire (1996; 2004), Martín-Barbero (2001), Pêcheux (1999), Bourdieu (2010; 1974; 1983; 1972), Canclini (1984; 1999), Hall (2005) e Goffman (1988).
Keywords: História - Estudo e ensino; Educação; Ensino audiovisual; History - Study and teaching; Education; Audio-visual education